Advantages of Routine Ultrasound Combined With Contrast-Enhanced Ultrasound in Diagnosing Papillary Thyroid Carcinoma. Issue 3 (September 2017) - Li, Fengsheng; Wang, Yunmei; Bai, Baoyan; Wang, Shengli; Liu, Shuguang
Abstract : Abstract: This study aimed to evaluate the advantages of routine ultrasound (US), contrast-enhanced US (CEUS), and the combination of these 2 methods in diagnosing papillary thyroid carcinoma (PTC). We subjected 89 patients with calcified thyroid nodules to conventional US and CEUS and then retrospectively analyzed the US and CEUS features of 89 patients with single, solid PTC. On this basis, we then evaluated the ability of US, CEUS, and their combination to diagnose PTC. In the 89 patients with thyroid nodules, US findings differed significantly from CEUS findings ( P < 0.05). In the US group, the diagnostic sensitivity, specificity, and accuracy were 87.5%, 78.8%, and 88.0%, respectively; in the CEUS group, these values were 92.9% ( P < 0.05), 87.9% ( P < 0.05), and 92.9% ( P < 0.05), respectively; and when the methods were combined, the diagnostic sensitivity, specificity, and accuracy were 96.7%, 92.7%, and 94.9%, respectively. A typical PTC nodule can be definitively diagnosed using US and CEUS; more specifically, the features of slow progression, late enhancement, and low enhancement were highly associated with a diagnosis of PTC. When these features were combined, they exhibited higher diagnostic performance than any individual method.